If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(3z + -1) = 18z + 45 Reorder the terms: 9(-1 + 3z) = 18z + 45 (-1 * 9 + 3z * 9) = 18z + 45 (-9 + 27z) = 18z + 45 Reorder the terms: -9 + 27z = 45 + 18z Solving -9 + 27z = 45 + 18z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-18z' to each side of the equation. -9 + 27z + -18z = 45 + 18z + -18z Combine like terms: 27z + -18z = 9z -9 + 9z = 45 + 18z + -18z Combine like terms: 18z + -18z = 0 -9 + 9z = 45 + 0 -9 + 9z = 45 Add '9' to each side of the equation. -9 + 9 + 9z = 45 + 9 Combine like terms: -9 + 9 = 0 0 + 9z = 45 + 9 9z = 45 + 9 Combine like terms: 45 + 9 = 54 9z = 54 Divide each side by '9'. z = 6 Simplifying z = 6
| 9(3z-1)=18z+45 | | 7/8*1/4 | | 2x^2+2y^2-12x+9=0 | | 16/5=x-12/25 | | -20-(4x-1)=-51 | | -3/5(7-4x)=25 | | 6x-12=9x-15 | | Xy(2y-3x)= | | -2y-10+2x=o | | gn=3*(-2)n-1 | | 2((5x^2)+8x-3)=0 | | -4x-(-5)/-7=13 | | 6x+3x+5=-7x+4-2 | | an=7+.2(n-1) | | 3v+1=4-4(2v-2) | | 1/5(3r-4)=3d | | 6/21-5/7 | | x^2-5x+-36=0 | | 4(3r-2)=(r+7) | | an=7+2(n-1) | | 5a+3-10a=3a+27 | | -2/-3x=20 | | 1/2x-1/2=3/4 | | -5.5x+-0.56=-1.64 | | 10k-50=6k-100 | | 2x+81=6x-121 | | 27=3x-42 | | m+(3m-15)=33 | | -5(4+2x)=50 | | 3n-1+2n=3n+3 | | 2x+81=6x+121 | | 4sqrt(3x)=16sqrt(3) |